Functions of head and body movements in Austrian sign language - Lackner, Andrea (Sign languages and deaf communities ;, 2017)
"Research on nonmanual elements or nonmanuals in sign languages has focused on both the possible functions and the occurrence (frequency and form) of these elements in recent years. As a matter of fact, research on nonmanuals is still a quite uncharted territory in Austrian Sign Language (OGS) today, which has also initiated the study given. In order to identify head and body movements in OGS, these nonmanuals were determined and analyzed functionally via a new user-oriented methodology. Getting feedback of multiple native signers was a main part of this method. Accordingly, you will find the findings of this study in this volume: various functions such as negation, assertion, interrogativity, conditionality, and many more can be expressed nonmanually. Brand new insights into sign language research are given, as well as astonishing results: even (epistemic) modality can be expressed by particular head and body movements"--